Ultrathin Printable Graphene Supercapacitors with AC Line‐Filtering Performance. (12th May 2015) - Wu, Zhong‐Shuai; Liu, Zhaoyang; Parvez, Khaled; Feng, Xinliang; Müllen, Klaus
Abstract : Ultrathin printable graphene supercapacitors are demonstrated, based on solution‐processed electrochemically exfoliated graphene hybrid films on an ultrathin poly(ethylene terephthalate) substrate, exhibiting an unprecedented volumetric capacitance of 348 F cm −3, an ultrahigh scan rate of 2000 V s −1, and AC line‐filtering performance.